INFLUENCE OF ORGANIZATIONAL CULTURE AND LEADERSHIP STYLE ON THE PERFORMANCE OF EMPLOYEES (Studies in Human Capital Group PT Bank Syariah Mandiri, Tbk.) - Pradana, Hafiz; R Sudiarditha, I Ketut; Waspodo, Agung AWS (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2015)
The purpose of this study are: 1) To find a description of the organizational culture, leadership style, and performance of employees at PT Bank Syariah Mandiri, Tbk. 2) To test empirically the influence of organizational culture on employee performance at PT Bank Syariah Mandiri, Tbk. 3) To test empirically the influence of leadership style on the performance of employees at PT Bank Syariah Mandiri, Tbk. 4) To test empirically the influence of organizational culture and leadership style simultaneously on the performance of employees at PT Bank Syariah Mandiri, Tbk. The analysis of this study is descriptive and explanatory analysis. Research conducted on 63 employees of PT Bank Syariah Mandiri, Tbk., while the data collection techniques is used an observation, interview, and questionnaire, which are processed using by SPSS 16.0. The result of the hypothesis shows that there is a positive and significant influence between organizational culture on performance as well as a positive and significant influence of leadership style on performance. Organizational culture and leadership style also have an influence simultaneously positive and significant effect on performance. Keywords: organizational culture, leadership style, performance, PT Bank Syariah Mandiri, Tbk.